Influence of Nonnutritive Sucking Habits on the Oral Carriage of Escherichia coli - Aseel Al Haidar (Hindawi Limited, 2022)
Objectives. This study aimed to evaluate the impact of nonnutritive sucking habits on the presence of oral Escherichia coli. Methods. One hundred and twenty children aged 3-5 years old were enrolled in the present case-control study, as follows: 60 children with continuous pacifier and thumb sucking habits (study group) and 60 children without any sucking habits (control group). The children in the two groups were matched in terms of age and gender. Information was gathered from the parents concerning their children using a special sheet. Sterile swabs were taken from both groups and cultured on agar plates. Then, they were subjected to further biochemical tests to identify E. coli species. The mean of the E. coli count was determined for each child. Descriptive, independent t-test and chi-square test statistics were used. The level of significance was set at p<0.05. Results. The presence of nonnutritive sucking habits was related to a higher carriage of E. coli among children. Conclusion. Nonnutritive sucking habits may act as a predisposing factor that enhances the colonization of oral E. coli.